Radial forearm flap versus antero-lateral thigh flap in oral soft tissue reconstruction: update and statistical analysis on our 77 consecutive cases for an objective selection criteria - Pinto, Valentina; Benanti, Elisa; De Maria, Federico; Pinelli, Massimo; Spaggiari, Antonio; De Santis, Giorgio (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: The radial forearm free flap (RFFf) and the antero-lateral thigh flap (ALTf) are considered the “key flaps” for oral cavity reconstruction. Nowadays, the literature lacks of an objective and standardized decision-making algorithm for the flap choice. The aim of this study is to describe a decision-making algorithm concerning the more appropriate flap, RFFf or ALTf, in the reconstruction of intra-oral soft tissues based on the volumetric analysis of the defect with a pre-operative Magnetic Resonance Imaging (MRI), updating our previous surgical experience. Methods: We conducted a retrospective observational study including 77 patients who underwent microsurgical reconstruction with RFFf or ALTf after tumor resection of the soft tissues in the oral cavity. During follow-up, patients were evaluated using the UW-QOL questionnaire. Results: Analyzing the scores of the UW-QOL questionnaire based on the size of the tumor on preoperative MRI we found that for tumor volume <50cc and between 50-70cc, the patients reconstructed with RFFfobtained statistically significant better scores compared to the ALTf group, while for tumor volume >70cc, the patients reconstructed with ALTf reported statistically significant better scores. Conclusions: Pre-operative RMI-guided volumetric assessment of oral cancer plays a key role in the planning of adequate soft tissue reconstruction and can objectively help surgeons in the correct choice of the flap (RFFf vs. ALTf) for each case based on preoperative tumor size, suggesting for defects <50cc and between 50 and 70 cc a reconstruction with RFFf, while for defects >70cc a reconstruction with ALTf.